Determinants of malaria infections among children in refugee settlements in Uganda. Analysis of data from Uganda malaria indicator survey, 2018-19 - Musoke, Henry S.; Liang, Song; Mukwaya, Paul Isolo; Mugagga, Frank; Swahn, Monica; Nseka, Denis; Wasswa, Hannington; Kayima, Patrick (Analysis of data from Uganda malaria indicator survey, 2023)
Globally, 5% of 247 million global malaria cases are reported Uganda which is also one of the top refugee hosting countries in Africa, with 1.36 million refugees currently. Although malaria is an emerging challenge for humanitarian response in refugee settlements, little is known about its risk factors. The study analysed data from the 2018-19 Uganda Malaria Indicator Survey (UMIS) to determine the factors associated with malaria infections among refugee children under ve years of age.